2018
DOI: 10.1111/gcb.14316
|View full text |Cite
|
Sign up to set email alerts
|

Temperature response of permafrost soil carbon is attenuated by mineral protection

Abstract: Climate change in Arctic ecosystems fosters permafrost thaw and makes massive amounts of ancient soil organic carbon (OC) available to microbial breakdown. However, fractions of the organic matter (OM) may be protected from rapid decomposition by their association with minerals. Little is known about the effects of mineral-organic associations (MOA) on the microbial accessibility of OM in permafrost soils and it is not clear which factors control its temperature sensitivity. In order to investigate if and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 93 publications
4
70
1
Order By: Relevance
“…1 forefield was between 0.21 and 0.30 µg CO 2 -C g −1 soil day −1 for the 40 day incubation period at 5°C. The CO 2 -C release rate was similar to soils that were measured in polar regions (including Barrett, Virginia, Parsons, & Wall, 2006;Gentsch et al, 2018) at the same incubation temperature, and it was much lower than that in permafrost (Chen et al, 2016;Knoblauch et al, 2013;Lee, Schuur, Inglett, Lavoie, & Chanton, 2012;Treat et al, 2014). The CO 2 -C release rates increased with deglaciation age, which was similar to the trend of the rates detected in the glacier forefield of Damma and North Iceland (Guelland et al, 2013;Wookey, Bol, Caseldine, & Harkness, 2002).…”
Section: Co 2 -C Release and Potential Feedback With Warmingsupporting
confidence: 78%
“…1 forefield was between 0.21 and 0.30 µg CO 2 -C g −1 soil day −1 for the 40 day incubation period at 5°C. The CO 2 -C release rate was similar to soils that were measured in polar regions (including Barrett, Virginia, Parsons, & Wall, 2006;Gentsch et al, 2018) at the same incubation temperature, and it was much lower than that in permafrost (Chen et al, 2016;Knoblauch et al, 2013;Lee, Schuur, Inglett, Lavoie, & Chanton, 2012;Treat et al, 2014). The CO 2 -C release rates increased with deglaciation age, which was similar to the trend of the rates detected in the glacier forefield of Damma and North Iceland (Guelland et al, 2013;Wookey, Bol, Caseldine, & Harkness, 2002).…”
Section: Co 2 -C Release and Potential Feedback With Warmingsupporting
confidence: 78%
“…Our temperature sensitivity results are contrary to predictions based solely on the carbon quality‐temperature (CQT) theory of decomposition (Aaltonen et al, 2019; Bosatta & Agren, 1999; Conant et al, 2011; Davidson & Janssens, 2006; Davidson et al, 2006). A growing body of literature recognizes a model of apparent temperature sensitivity that is determined by interactions between substrates, microbial communities, and abiotic variables (Bosatta & Agren, 1999; Conant et al, 2011; Dungait et al, 2012; Gentsch et al, 2018; Gillabel, Cebrian‐Lopez, Six, & Merckx, 2010; Kleber et al, 2011; Moinet et al, 2018; Tang, Cheng, & Fang, 2017; Wagai et al, 2013; Zimmermann, Leifeld, Conen, Bird, & Meir, 2012). Thermal alteration of SOM by fire has been shown to alter the temperature sensitivity of microbial respiration in peatlands, which has important implications for the response of peatland carbon cycles to climate change (Chen et al, 2018; Davidson & Janssens, 2006; Holden et al, 2016; O'Donnell et al, 2009; Sawamoto, Hatano, Yajima, Takahashi, & Isaev, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Our work supports a depth x Fe interaction effect on AOM rates, which could be explained as: (1) CH 4 production suppression in shallow soils by the presence of oxygen, and in deeper soils by substrate limitation; (2) decreased production due to high concentrations of Fe in the deeper soil layers; and/or (3) increased Fe-AOM in the deeper layers where concentrations of both CH 4 and Fe are highest. The presence of Fe and other mineral species in the deeper soil layers could contribute to substrate-related depressions in production, as mineral-organic associations protect soil organic carbon from decomposition [88]. There is also evidence that organic-and mineral-CH 4 associations in deeper soil layers have a complex relationship with temperature, where warmer anoxic soils could result in higher rates of non-methanogenesis redox [83], particularly salient to net fluxes from warming permafrost peat soils.…”
Section: Drivers and Stressorsmentioning
confidence: 99%
“…For example, Tan et al [83] found a temperature-dependent inhibitory effect of humic substances on methane production in peat soils, while Valenzuela et al [80] proved that humic substances can act as an electron acceptor for AOM in wetland soils. We know that warming will promote permafrost thaw, thus increasing the availability of complex soil carbon species (e.g., humic substances) and minerals for metabolic use [88][89][90]. It is unknown how the full suite of changing dynamics of the active layer will interact with CH 4 cycling, as it seems likely that increased humic substance concentrations could inhibit methanogenesis, while also promoting AOM activities.…”
Section: Drivers and Stressorsmentioning
confidence: 99%